Dopamine, Noradrenaline and Differences in Sexual Behavior between Roman High and Low Avoidance Male Rats: A Microdialysis Study in the Medial Prefrontal Cortex - Sanna, Fabrizio; Bratzu, Jessica; Piludu, Maria A.; Corda, Maria G.; Melis, Maria R.; Giorgi, Osvaldo; Argiolas, Antonio (Frontiers in Behavioral Neuroscience, 2017)
Roman High- (RHA) and Low-Avoidance (RLA) outbred rats, which differ for a respectively rapid vs. poor acquisition of the active avoidance response in the shuttle-box, display differences in sexual activity when put in the presence of a sexually receptive female rat. Indeed RHA rats show higher levels of sexual motivation and copulatory performance than RLA rats, which persist also after repeated sexual activity. These differences have been correlated to a higher tone of the mesolimbic dopaminergic system of RHA rats vs. RLA rats, revealed by the higher increase of dopamine found in the dialysate obtained from the nucleus accumbens of RHA than RLA rats during sexual activity. This work shows that extracellular dopamine and noradrenaline also, increase in the dialysate from the medial prefrontal cortex of male RHA and RLA rats put in the presence of an inaccessible female rat and more markedly during direct sexual interaction. Such increases in dopamine (and its main metabolite DOPAC) and noradrenaline were found in both sexually naïve and experienced animals, but they were higher i) in RHA than in RLA rats and ii) in sexually experienced RHA and RLA rats than in their naïve counterparts. Finally, the differences in dopamine and noradrenaline in the medial prefrontal cortex occurred concomitantly to those in sexual activity, as RHA rats displayed higher levels of sexual motivation and copulatory performance than RLA rats in both the sexually naïve and experienced conditions. These results suggest that a higher dopaminergic tone also occurs in the medial prefrontal cortex, together with an increased noradrenergic tone, which may be involved in the different copulatory patterns found in RHA and RLA rats, as suggested for the mesolimbic dopaminergic system.